Relief of hypoxia by angiogenesis promotes neural stem cell differentiation by targeting glycolysis. (8th February 2016) - Lange, Christian; Turrero Garcia, Miguel; Decimo, Ilaria; Bifari, Francesco; Eelen, Guy; Quaegebeur, Annelies; Boon, Ruben; Zhao, Hui; Boeckx, Bram; Chang, Junlei; Wu, Christine; Le Noble, Ferdinand; et al.
Abstract: Blood vessels are part of the stem cell niche in the developing cerebral cortex, but their in vivo role in controlling the expansion and differentiation of neural stem cells (NSCs) in development has not been studied. Here, we report that relief of hypoxia in the developing cerebral cortex by ingrowth of blood vessels temporo‐spatially coincided with NSC differentiation. Selective perturbation of brain angiogenesis in vessel‐specific Gpr124 null embryos, which prevented the relief from hypoxia, increased NSC expansion at the expense of differentiation. Conversely, exposure to increased oxygen levels rescued NSC differentiation in Gpr124 null embryos and increased it further in WT embryos, suggesting that niche blood vessels regulate NSC differentiation at least in part by providing oxygen. Consistent herewith, hypoxia‐inducible factor (HIF)‐1α levels controlled the switch of NSC expansion to differentiation. Finally, we provide evidence that high glycolytic activity of NSCs is required to prevent their precocious differentiation in vivo . Thus, blood vessel function is required for efficient NSC differentiation in the developing cerebral cortex by providing oxygen and possibly regulating NSC metabolism. Synopsis: Blood vessel formation in mammalian brain development promotes neural stem cell differentiation by triggering a cascade of tissue oxygenation, reduced activity of HIF‐1α and blunted glycolytic metabolism that favors the switch towards neurogenesis. An animated version of this synopsis is available online at:http://embopress.org/video_EMBOJ-2015-92372 . Absence of blood vessels reduces neural stem cell (NSC) differentiation in development. Restoring oxygenation rescues NSC differentiation in the absence of normal vessels. HIF‐1α levels regulate the switch of NSC expansion to differentiation in the cortex. The glycolytic regulator and HIF target gene Pfkfb3 is critically required for normal NSC expansion and upon HIF‐1α stabilization. Abstract : Blood vessel formation in mammalian brain development promotes neural stem cell differentiation by triggering a cascade of tissue oxygenation, reduced activity of HIF‐1α and blunted glycolytic metabolism that favors the switch towards neurogenesis.